One Year After Enrollment in Literacy Programs: A Study of Changes in Learners' Lives - Richard Edwards; Robin Usher (Adult Education Research Conference, 2000)
In this paper, we argue that moves to reconfigure the education of adults as a dimension of lifelong learning signify a postmodern condition of education. In particular, we suggest that lifelong learning contributes to performativity and a loss of mastery, while at the same time opening up different possibilities for adult learners. This poses complex challenges to adult educators.